Best Practices for Hospital's Core Marketing - Hodijah, Cucu; Maria, Santi; Santo Dewatmoko (Escalate : Economics and Business Journal, 2023)
The purpose of this study was to examine Hermina Hospital Sukabumi's approach to specialization in maternal and child healthcare as a core marketing strategy. The methodology involved gathering perspectives from the Board of Directors and specialist doctors to identify challenges and opportunities. Findings revealed that financial considerations, regulatory requirements, skill development, and patient care coordination were key challenges. To enhance core marketing, recommendations include investments in advanced medical technology, continuous staff training, expanded telehealth services, community engagement, and robust feedback mechanisms. These initiatives aim to solidify the hospital's leadership in maternal and child healthcare, attract and retain patients, and ensure the delivery of the highest standard of care. In conclusion, a patient-centered approach, ongoing improvement, and innovative strategies are crucial for achieving specialization in maternal and child healthcare, contributing to Hermina Hospital Sukabumi's long-term success in providing top-quality care to mothers and children.